2022
DOI: 10.3390/nu14112254
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Consumption of Relevant Immune System Micronutrients Is Associated with a Worse Impact of COVID-19 in Spanish Populations

Abstract: Coronavirus disease 2019 (COVID-19) has caused a global health crisis and the factors behind its differential impact on COVID-19 among populations are still being known. Geographical differences in nutrient profile could be a relevant factor, especially considering that scientific evidence supports that 10 micronutrients are essential for proper immune system function. This study aims to evaluate these micronutrient intakes in the territories of Spain and to analyze their relationship with epidemiological indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…The Spanish group of Prof. Francisca Serra submitted, in July 2020, a “current state of evidence” review dealing with the nutritional and nutrigenetic factors that affect immunity; it included a compilation of COVID-19 epidemiological data that were available at the time (May 2020) in 10 European countries, showing a non-significant inverse correlation between the suboptimal estimated status of selenium and COVID-19 incidence [ 27 ]. Later, the same group focused on the estimated selenium intake in Spain and did not find any significant association with the epidemiological indicators of COVID-19 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Spanish group of Prof. Francisca Serra submitted, in July 2020, a “current state of evidence” review dealing with the nutritional and nutrigenetic factors that affect immunity; it included a compilation of COVID-19 epidemiological data that were available at the time (May 2020) in 10 European countries, showing a non-significant inverse correlation between the suboptimal estimated status of selenium and COVID-19 incidence [ 27 ]. Later, the same group focused on the estimated selenium intake in Spain and did not find any significant association with the epidemiological indicators of COVID-19 [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamins C and D, alongside other essential nutrients, can help with the ‘maintenance of functions of the immune system’ (European Food Safety Authority, EFSA) [ 57 ]; thus, mitigating deficiency risks for these during the early stages of the novel coronavirus pandemic was emphasized [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Research on vitamin C and vitamin D status remains ongoing on the grounds that their deficiency may be associated with increased susceptibility to COVID-19 infection and to potentially more severe or prolonged symptoms once infected [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. Because medical prescription is not needed for their procurement, misinformed assurances with silent contraindications about vitamin supplements could lead to harmful intakes, unsafe combinations, and misuse by the public, as seen in hypervitaminosis and intoxication case reports during the global pandemic [ 36 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of various studies showed that this vitamin could affect the reduction in the activity of various infectious viruses, especially the coronavirus, and increase the body's immunity 28 . Also, published evidences around the worlds, showed that various diets and different micronutrients play a role in the immune system and COVID‐19 patients 29–32 …”
Section: Discussionmentioning
confidence: 99%
“…28 Also, published evidences around the worlds, showed that various diets and different micronutrients play a role in the immune system and COVID-19 patients. [29][30][31][32] This research was the first study in Iran with this comprehensiveness and a high sample size in order to determine the association between important macronutrients (such as proteins, fats, carbohydrates, and fiber), micronutrients (such as vitamins and antioxidants), the infection of COVID-19, and hospitalization due to it, which, of course, had several limitations. Among these limitations, we can point out the presence of various confounding factors related to different food and diets, which could not be controlled in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation